2018
DOI: 10.1021/acscatal.8b00151
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile and Highly Z-Selective Olefin Metathesis Ruthenium Catalyst Based on a Readily Accessible N-Heterocyclic Carbene

Abstract: A ruthenium catalyst for Z-selective olefin metathesis has been synthesized from a readily accessible N-heterocyclic carbene (NHC) ligand that is prepared thanks to an efficient, practical and scalable multicomponent synthesis. The desired ruthenium complex with cyclometalated NHC ligand is obtained by means of selective C(sp 3)-H activation at the adamantyl fragment and X-ray diffraction analysis unambiguously confirmed the structure of the precatalyst. The catalyst demonstrated attractive catalytic performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 56 publications
2
60
0
Order By: Relevance
“…Although some advances have been achieved using phosphine ligands, their tedious synthesis and, in some cases, intrinsic ease of oxidation excludes practical applications on a large scale. In contrast, the rigid structure of NHCs (N-heterocyclic carbenes) provides an excellent opportunity to form stable gold complexes with a well-defined chiral environment, as was proven in the case of other metals, such as palladium [26][27][28][29], ruthenium [30][31][32][33] or copper [34][35][36][37][38][39][40][41][42]. Moreover, adequately planned structure of NHC ligands allows for tuning of their electronic and steric properties, which is not easily achievable in the case of phosphines [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Although some advances have been achieved using phosphine ligands, their tedious synthesis and, in some cases, intrinsic ease of oxidation excludes practical applications on a large scale. In contrast, the rigid structure of NHCs (N-heterocyclic carbenes) provides an excellent opportunity to form stable gold complexes with a well-defined chiral environment, as was proven in the case of other metals, such as palladium [26][27][28][29], ruthenium [30][31][32][33] or copper [34][35][36][37][38][39][40][41][42]. Moreover, adequately planned structure of NHC ligands allows for tuning of their electronic and steric properties, which is not easily achievable in the case of phosphines [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, unsymmetrical heterocyclic carbenel igands (uNHC;F igure 1b)p roved to be highly amenable for modifications, yielding an umber of new Ru catalysts tailoredf or challenging metathesis transformations such as ethenolysis, selfmetathesis of a-olefins, or macrocyclization reactions. [11,12] Independently,u NHC ligandsh ave allowed the development of Zselective [13] and enantioselective Ru catalysts. [12e, 13d, 14] In our previouss tudies on benzyl-substitutedu NHC (e.g., L2), we found that an increaseoft he steric bulk of the N-aromatic substituent,b yr eplacing Mes with DIPP,b rought promising enhanceds electivity to the catalysts derived from such alteredl igands, however at the cost of slightly diminished activity.…”
Section: Introductionmentioning
confidence: 99%
“…Under the same reaction conditions, the saturated ligand L11 was inapplicable as predominant alkene isomerization occurred. On the other hand, its unsaturated ligand analogue L14 could prevent alkene isomerization [44] and afforded the desired product 40 a in good 52 % yield and enantioselectivity (76 % ee). Further ligand screening evidenced the bulky acenaphthene-based NHC L17 as the most efficient ligand affording 40 a in nearly quantitative yield and high 97 % enantiomeric excess.…”
Section: Methodsmentioning
confidence: 99%